Cardiac recovery via extended cell-free delivery of extracellular vesicles secreted by cardiomyocytes derived from induced pluripotent stem cells. (May 2018) - Liu, Bohao; Lee, Benjamin; Nakanishi, Koki; Villasante, Aranzazu; Williamson, Rebecca; Metz, Jordan; Kim, Jinho; Kanai, Mariko; Bi, Lynn; Brown, Kristy; Di Paolo, Gilbert; Homma, Shunichi; et al.
Abstract The ability of extracellular vesicles (EVs) to regulate a broad range of cellular processes has recently been exploited for the treatment of diseases. For example, EVs secreted by therapeutic cells injected into infarcted hearts can induce recovery through the delivery of cell-specific microRNAs. However, retention of the EVs and the therapeutic effects are short-lived. Here, we show that an engineered hydrogel patch capable of slowly releasing EVs secreted from cardiomyocytes (CMs) derived from induced pluripotent stem cells reduced arrhythmic burden, promoted ejection-fraction recovery, decreased CM apoptosis 24 h after infarction, and reduced infarct size and cell hypertrophy 4 weeks post-infarction when implanted onto infarcted rat hearts. We also show that EVs are enriched with cardiac-specific microRNAs known to modulate CM-specific processes. The extended delivery of EVs secreted from induced-pluripotent-stem-cell-derived CMs into the heart may help us to treat heart injury and to understand heart recovery. A hydrogel patch for the sustained delivery of extracellular vesicles from cardiomyocytes derived from induced pluripotent stem cells improves tissue regeneration in infarcted rat hearts.